Orientation Effect on Statics and Natural Frequency of Cantilever Beam - Ardi Noerpamoengkas; Miftahul Ulum; Ahmad Yusuf Ismail (universitas teuku umar, 2020)
Statics and frequency analyzes are important because the structure can support the static and dynamic loads. Most previous studies of statics and frequency did not involve the gravity load. The previous studies of gravity effect to the cantilever beam included the hanging, horizontal, and inverted positions. The gravity load direction is applied referred to the longitudinal and lateral beam directions in this study. The closer to the inverted position the smaller the natural frequency. The highest values of the maximum displacement and the maximum Von-Mises stress are happened if longitudinal position is horizontal and lateral orientation angle is 0°. The change of lateral orientation angle does not influence the natural frequency in this condition. Keywords—Cantilever beam, gravity load, natural frequency, orientation angle, statics